2014
DOI: 10.1186/s12933-014-0109-8
|View full text |Cite
|
Sign up to set email alerts
|

High carbohydrate and high fat diets protect the heart against ischaemia/reperfusion injury

Abstract: BackgroundAlthough obesity is still considered a risk factor in the development of cardiovascular disorders, recent studies suggested that it may also be associated with reduced morbidity and mortality, the so-called “obesity paradox”. Experimental data on the impact of diabetes, obesity and insulin resistance on myocardial ischaemia/reperfusion injury are controversial. Similar conflicting data have been reported regarding the effects of ischaemic preconditioning on ischaemia/reperfusion injury in hearts from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 50 publications
(82 reference statements)
9
41
0
Order By: Relevance
“…In addition, the insulin levels were even lower in HFLCD that in control group. diet and HFD) in Wistar rats resulted in cardioprotection against acute ischemia/reperfusion damage and in the activation of the RISK pathway in an ex vivo model, thus supporting the findings of the present study [41]. The term insulin resistance implies an inadequate effect of insulin on glucose metabolism, but does not address other aspects of insulin action.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the insulin levels were even lower in HFLCD that in control group. diet and HFD) in Wistar rats resulted in cardioprotection against acute ischemia/reperfusion damage and in the activation of the RISK pathway in an ex vivo model, thus supporting the findings of the present study [41]. The term insulin resistance implies an inadequate effect of insulin on glucose metabolism, but does not address other aspects of insulin action.…”
Section: Discussionsupporting
confidence: 88%
“…The paradox has also been described in type 2 diabetic patients with cardiovascular co-morbidity, in whom overweight and obesity may enhance survival in a setting of insulin-resistant diabetes [32]. Animal studies have confirmed the increased resistance to ischemic heart injury in obese, as well as lean, type 2 diabetic rats and rabbits [3335], as well as in rats [11] and mice fed a HFD [36, 37]. Despite these findings, the existence and relevance of obesity-dependent cardioprotection remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data imply that an obesogenic high fat diet enhance myocardial tolerance against ischemic-reperfusion induced injury (IR), but this cardioprotection was not associated with activation of ERK p44/p42 or PKB/Akt dependent RISK signaling (reperfusion injury salvage kinase pathway) [11], a pathway widely accepted to mediate protection against reperfusion injury [12, 13]. Furthermore, a recent study by Salie et al suggests that hearts protected by obesogenic diets are unresponsive to additional cardioprotective conditioning maneuvers, such as ischemic preconditioning (IPC) or β-adrenergic preconditioning (β-PC), indicating that the hearts were maximally protected by the diets [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with this, ex vivo hearts from high fat-fed mice subjected to ischemia-reperfusion showed increased infarct size. Although the literature supports that long-term HFD feeding is associated with increased infarct size (29,49), there are also studies reporting reduced infarct size following obesogenic diets (13,41). Factors such as differences in age, diet composition, and feeding period, as well as ex vivo perfusion conditions (i.e., energy substrate composition), may contribute to some of these discrepancies.…”
Section: Discussionmentioning
confidence: 99%